Improving the Automotive Roof Adhesive Sealing Process: A Case Study of a Sample Company - อักษรธรรม สมจินต์; ชิดสนิท กำพล; คิดนอก อุรุมาท (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to investigate the problems in the automotive roof adhesive sealing process and to reduce operational waste. The researcher analyzed the existing conditions by studying the work procedures and applying a fishbone diagram to identify root causes. The findings revealed that excessive walking and frequent handling were major issues. Improvements were made by redesigning and repositioning the adhesive gun holder. In addition, the problem of repeatedly picking up tools and equipment was addressed by using a 7 mm nozzle and eliminating the use of the 2 mm nozzle. The results showed that the number of steps required to seal one automotive roof was reduced from the original process to 19 steps, a reduction of 5 steps. Unnecessary walking was reduced from 21 steps to 15 steps, decreasing by 6 steps. Furthermore, the processing time per vehicle was reduced from 0.954 minutes to 0.757 minutes.